Dyplomacja brytyjska wobec przystąpienia ZSRS do Ligi Narodów w 1934 r. - Jeziorny, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 2012)
First rumors about Moscow’s access to the League of Nation appeared after the whole series of speeches delivered by the Soviet leading personalities at the turn of 1933/1934. It was regarded as a revolutionary step because the USSR’s attitude towards the League has been very hostile so far. Deterioration of Soviet-German relations in 1933 after the Reichstag’s fire made the Soviet authority willing to cooperate with Geneva. London was not sure about the Soviet attitude in this question but Lord Chilston, British Ambassador in Moscow tended to state that the USSR was going at least to cooperate with the League of Nations. Diplomats employed in the Northern Department of the Foreign Office, who commented Chilston’s reports, did not doubt that Moscow moved to the “anti-revisionist camp”. However higher FO officials were more reserved. Sir John Simon, the Secretary and Sir Robert Vansittart, the Permanent Under-Secretary regarded the Soviet enuntiations as tactical only. Their suspicions were strong because Moscow has never clearly declared her intentions. In Spring 1934 British Foreign Office experienced pressure from various sides to support the Soviet access to the League of Nations. It was mainly the French government which was not going to be the only Moscow’s mentor. Sir John Simon declared in the House of Commons his support for the Soviet accession to the League of Nations after Louis Barthou’s visit to London. He described the USSR as a big power with a hugh potential. Its League membership was labelled as a condition for stabilizing world political situation. The only diplomatic démarche addressed to London was taken up by the Soviet diplomacy on 3rd August 1934. The British response was very promising so Moscow did not try influence Paris and London more actively. French diplomacy assisted by strong British support brought the USSR in the League of Nations on 18th September. The Soviet conditions (particularly official invitation from Geneva powers and guarantee of a permanent seat in the League’s Council) were not too difficult to be fulfilled for the British Cabinet.